Ghirah dalam Tafsir fi Zilal Al-Qur’an (Analisis Semangat Bela Agama pada QS Al-An’am Ayat 68-70) - Zuhriyandi; Mumtaz Ibnu Yasa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This article addresses what should be done when one’s religion is insulted or harassed. Namely the spirit of passion or jealousy when one’s religion is insulted. This problem is caused by the large number of cases of insults against the Islamic religion. Sayyid Qutb’s thoughts were used as the basis, because he was an Islamic reformer and active against tyranny. For this reason, this article contains several problems: a.) what is meant by ghirah?; b.) how is the interpretation of QS. al-An’am verses 68-70 in the interpretation of Fi Zilal Al-Qur’an?; and c.) how is the relationship between ghirah and the spirit of defending religion in QS. al-An’am verses 68-70? The research uses a literature-based qualitative approach. As for the results of this research: first, Sayyid Qutb interpreted this verse as a command to Muslims to let people who make fun of religion, cut ties with them and avoid them. Apart from just reminding, correcting deviant opinions within the boundaries of muamalah. Second, defending religion cannot be separated from the obligations of every Muslim. Religious followers certainly will not accept it if their religion is insulted. The order to distance oneself and not associate with religious mockers is a response based on feelings of enthusiasm for the spirit of defending one’s religion. The implications of the research can provide direction for Muslims in navigating these challenges in a way that is in accordance with Islamic teachings and inspires a strong attitude in defending the truth of their religion.